Government Motives for Privatizing Public Schools in Punjab: Exploring Teachers’ Precarity and Educational Equity - Hayat, Khizer (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
The pros and cons of privatizing education have long been a topic of discussion among policymakers across the globe. The privatization attempts of public schools by the Punjab government are episodic but persist, resulting in a sufficient amount of tension for teachers and countless concerns about educational equity. The study aims to identify the current motives of the government by discovering the driving forces behind privatization and evaluating the job security issues for teachers and academic quality for students of all socioeconomic levels. Semi-structured interviews were conducted in this study, utilizing a qualitative research approach to learn about teacher perspectives from 2 public school teachers and 2 private school teachers from diverse areas within Punjab to know diverse opinions. Respondents belong in Punjab, where public schools have been privatized. Besides, document analysis was used to compare and contrast government policy motives delving further into the issue. The study’s findings show that the government’s objectives for privatization include cost reduction, increased efficiency, and a desire to attract private investment. However, privatization efforts have resulted in a decrease in employment security for public school teachers and educational equity for students belonging to underprivileged families. Privatization can undoubtedly have cost-effective short-term effects, but it also puts educational equity and teachers’ well-being in jeopardy. Thus, the study proposes that policymakers carefully consider long-term solutions that uphold teachers’ rights and prioritize education for all.